Stability and Bifurcation Analysis of the Nutrient-Microorganism Model (Journal of Nonlinear Modeling and Analysis, 2024)
Stability analysis and bifurcation of the nutrient-microorganismmodel are presented in this paper. It is found that the model could experiencethe changes of the equilibrium points and the saddle-node, the Hopf and thecodimension-2 Bogdanov-Takens bifurcations. The induced complex dynamicsare also illustrated, by virtue of theory like the Sotomayor’s theorem, thenormal form and the universal unfolding. From the obtained results, someinsights into interaction between the nutrient and the microorganism can begiven. Further, numerical simulation is carried out to verify the theoreticalresults.
Keywords: Nutrient-microorganism model; coexistence; Bogdanov-Takens bifurcation.